Boundary spanners in inter-organizational relationships: A literature review and research agenda - Ernando Fagundes; Valdirene Gasparetto (BBR: Brazilian Business Review, 2023)
The literature on interorganizational relationships has explored them at the organizational level and ignored interpersonal relationships. This paper consists of a literature review analyzing, consolidating, and synthesizing studies on boundary spanners in business-to-business (B2B) interorganizational relationships, pointing out directions for future research. The review was carried out in ten steps, separated into three phases encompassing planning, collecting, and synthesizing data, and disclosing the results. The study assesses 3,156 published articles, and 45 of them addressed the theme of boundary spanners in B2B interorganizational relationships. These articles were analyzed, identifying their characteristics and the evolution of research through time. The definitions of interpersonal and interorganizational relationships were compared, observing how the literature has addressed the interdependency between these relationships. Also, the concepts and roles assigned to boundary spanners were analyzed, leading to an integrated framework of the existing literature on the theme. Finally, suggestions for future research are presented, followed by this review’s implications and limitations.